The Performance Analysis of Dynamic Investment Portfolio Insurance Strategies Based on Value at Risk - Alkhalidi, fatima Faisal; Mohammed, Ayad Tahir (Journal of Economics and Administrative Sciences, 2025)
The research aims to address the fundamental problem by reducing the systematic risks to which investments in the stock market are exposed and to benefit from the emerging potential provided by investment portfolio insurance strategies, through Value at Risk Based Portfolio Insurance (VBPI), using the comparative analytical approach. The research community was represented by the (ISX60) index, The data was collected through the annual reports of the Iraq Stock Exchange to form three intentional yearly conditional samples for the period (2022-2024), and several financial models were relied upon, such as Simple Ranking, Single Index, Sharpe, and Treynor Models. Several results were reached, as the efficient dynamic investment portfolio before insurance according to the Sharpe model outperformed the VBPI. At the same time, the VBPI succeeded in achieving a performance level according to the Treynor model on the uninsured portfolio. The originality of the research lies in building three efficient dynamic investment portfolios and insuring them according to the Value at Risk Model as a new strategy in insuring investment portfolios.